Memory, event, object and place: Memory, event, object and place - Pérgolis Valsecchi, Juan Carlos (Corporación Universitaria del Caribe, CECAR., 2019)
In this investigation, carried out to be presented at the Ernesto Restrepo Tirado Annual Chair of History, of the National Museum, Bogotá, Colombia, an attempt is made to review the dualities space / place; history / memory; and official story / multiple stories, based on the following hypothesis: 1. Events convert spaces into places, therefore, into “places of memory”; 2. History proposes a unique official account; memory draws on multiple stories. In this text, these hypotheses are observed in three places: the historic Puente de Boyacá, the Puente del Común and the urban bridge at 116th Street with Boyacá Avenue, in Bogotá. To conclude, they are observed in graffiti, as an ephemeral memory exercise; and at the Prometeo de la Libertad monument, by Arenas Betancourt, in Ciénaga, Magdalena. Finally, a reflection on the presence of the object of the memory is attempted, through the intervention on the pier of Puerto Colombia, Atlántico.